Collective Intertemporal Decisions and Heterogeneity in Groups - Daniela Glätzle-Rützler; Philipp Lergetporer; Matthias Sutter (Center for Economic Studies and ifo Institute (CESifo), 2019)
Many important intertemporal decisions, such as investments of firms or households, are made by groups rather than individuals. Little is known what happens to such collective decisions when group members have different incentives for waiting, because the economics literature on group decision making has, so far, assumed homogeneity within groups. In a lab experiment, we study the causal effect of group members' heterogeneous payoffs from waiting on intertemporal choices. We find that three-person groups behave more patiently than individuals and that this effect is driven by the presence of at least one group member with a high payoff from waiting. We present group chat content, survey data, and additional treatments to uncover the mechanism through which heterogeneity in groups increases patience.
Keywords: C91; C92; D03; D90; 330; patience; time preferences; group decisions; payoff heterogeneity; experiment